Automation research of thermal and physical characteristics of particulate-filled epoxy composites - Dobrotvor, I.G.; Stukhlyak, D.P.; Buketov А.V.; Mykytyshyn, A.G.; Zolotyi, R.Z.; Totosko, O.V. (Bulletin of the Karaganda University. Mathematics Series, 2018)
Thermal - physical characteristics of filled epoxy composites were investigated by means of the developed device which allowed to do computer - aided research within defined temperature range. Forward and reverse run of relative linear elongation factor of the sample (T,q)=∆1/1 at heating rate 1,5-2 K/min. and cooling rate 2,5-3 K/min. for the composites with particulate filler has been studied. Laplacian operator to scalar field eu and ed was used, which enables to derive stationarity or quasi - stationarity 2D areas of relaxation of macromolecular stress. Automation research will allow to determine the parameters of temperatures and filler content corresponding to minimal stress values. In the first approximation these are the following areas: 30<q<50, 385<T<395 K and 60<q<90, 340<T<380 K. Relaxation processes at the above - mentioned parameters are the most intensive in the composite. Such composites have the lowest residual stress.